Stickstoff basierte Flammschutzmittel für das Lasersintern: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Hücker, Lars

Phosphorhaltige Lasersinter-Materialien mit Flammschutzwirkung: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Schulz, Maurice

Flowability of polymer powders at elevated temperatures for additive manufacturing - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Rüther, Torben; Schmid, Hans-Joachim (Powder Technology)
Keywords: General Chemical Engineering

Entwicklung einer Methode zur Integration der Additiven Fertigung in die Serienproduktion am Beispiel des Lasersinterns - Kruse, Anne

Umsetzung einer optimierten Oberflächenschlitzung zur Wirbelstromverlustreduktion auf der Oberfläche eines additiv gefertigten Permanentmagnet-Rotors - Haase, Michael; Bieber, Maximilian; Tasche, Frederik; Schaper, Mirko; Hoyer, Kay-Peter; Ponik, Bernd; Magyar, Balázs (Proceedings of the 19th Rapid.Tech 3D Conference Erfurt, Germany, 9–11 May 2023)

Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Influence of the filler–matrix adhesion and the effects of conditioning on tensile properties of laser-sintered parts built with polyamide–glass bead dry blends - Kletetzka, Ivo; Kosanke, Maren; Meinderink, Dennis; Neßlinger, Vanessa; Grundmeier, Guido; Schmid, Hans-Joachim (Progress in Additive Manufacturing)
In this work, the influence of the filler–matrix adhesion on the tensile properties of laser-sintered parts built with Polyamide 613 filled with glass beads was investigated. For this purpose, dry blends of glass beads with and without organosilane coupling agents and polyamide powder were prepared and processed into tensile specimens on an EOS P396 laser sintering system. The samples were tested both in the dry state and after an accelerated conditioning in a climate chamber. Furthermore, finite element method (FEM) simulations were performed to model the extreme cases of optimum adhesion and no adhesion. By correlating the tensile tests with the simulation results and by analyzing the fracture surfaces, it was shown that the filler–matrix adhesion is sufficient in the dry state but is strongly degraded by conditioning. Even the presence of various organosilane thin films could not prevent a strong deterioration of the filler–matrix adhesion and the associated deterioration of the mechanical properties. Since a comparison with an injection-molded sample of the same polymer filler combination shows identical behavior after conditioning, it is assumed that this problem is not limited to additively manufactured parts.
Keywords: Industrial and Manufacturing Engineering

Influence of the filler matrix adhesion and the effects of conditioning on tensile properties of laser sintered parts built with polyamide glass bead dry blends - Kletetzka, Ivo; Kosanke, Maren; Meinderink, Dennis; Neßlinger, Vanessa; Grundmeier, Guido; Schmid, Hans-Joachim
Abstract In this work, the influence of the filler matrix adhesion on the tensile properties of laser-sintered parts built with Polyamide 613 filled with glass beads was investigated. For this purpose, dry blends of glass beads with and without organosilane coupling agents and polyamide powder were prepared and processed into tensile specimens on an EOS P396. The samples were tested both in the dry state and after an accelerated conditioning in a climate chamber. Furthermore, FEM simulations were performed to model the limiting cases of optimum adhesion and no adhesion. By correlating the tensile tests with the simulation results and by analyzing the fracture surfaces, it was shown that the filler matrix adhesion is sufficient in the dry state but is strongly degraded by conditioning. Even the presence of various organosilane thin films could not prevent a strong deterioration of the filler-matrix adhesion and the associated deterioration of the mechanical properties. Since a comparison with an injection molded sample of the same polymer filler combination shows identical behavior after conditioning, it is assumed that this problem is not limited to additively manufactured parts.

Tensile Testing for Polymer AM - Best Pratice at the DMRC - Kletetzka, Ivo

Influence of a prolonged shelf time on PA12 laser sintering powder and resulting part properties - Klippstein, Sven Helge; Kletetzka, Ivo; Sural, Ilknur; Schmid, Hans-Joachim (The International Journal of Advanced Manufacturing Technology)
In the laser sintering technology, the semi-crystalline polymer material is exposed to elevated temperatures during processing, which leads to serious material ageing for most materials. This has already been investigated intensively by various authors. However, the ageing of the material at ambient temperatures during shelf life has not been the focus so far. The need to analyse the shelf life can be derived from an ecological and economic point of view. This work is focusing on the shelf life of PA2200 (PA12). To reduce the potential influences of powder production fluctuations, two different powder batches stored for 5.5 years and 6.5 years are investigated and compared to a reference powder produced 0.5 years before these investigations. Multiple powder analyses and part characterisations have been performed. A significant yellowing and molecular chain length reduction can be derived from the measurement results. Whereas the influence on mechanical part performance was minor, the parts built with the stored powders are more yellowish. As it is most likely that this is due to the consumption of polyamide stabilisers, it can be assumed that these parts will be subject to significantly faster ageing. Therefore, it is still not recommended to use the stored powders for critical parts or light intense and humid environments.
Keywords: Selective laser sintering; Shelf life; Polyamide 12; powder; PA2200; material ageing